Rezim Global dan Liberalisasi Perdagangan Sektor Garam di Indonesia - Esti Renatalia Tanaem; Puguh Toko Arisanto (Universitas Islam Darul Ulum Lamongan, 2020)
Known as a maritime country, Indonesia is still unable to meet its need of salts, especially industrial salts. As a result, Indonesia has to import salts from various countries with an increasingly higher volume each year. Using theory of two-level games, authors found that the salt importing policy cannot be separated from international pressures so that Indonesia undertakes trade liberalization on salt sector. The international pressure emanated from three global regimes namely WTO, IMF and FTA. The three global regimes basically require Indonesia to liberalize its domestic market by removing tariff and non-tariff trade barriers in various sectors including salt. This paper will explain the mechanism and scheme of the three global regimes in liberalizing Indonesia's trade on salt sector.